WPSI-3 Characteristics of the feather developing pattern of early-feathering chicks and late-feathering chicks. (7th December 2018) - Sohn, S; Bang, M; Cho, E
Abstract: Chicken feathers were classified into early-feathering(EF) and late-feathering(LF) depending on the development and patterns of the wing feathers and tail feathers. Currently, the feather-sexing which is based on the differences in the feather developing at hatch is widely used sexing methods of chicks. The industrial application of feather-sexing to Korean native chickens(KNC) has not been reported yet. This study was conducted to investigate the classification of EF and LF in KNC. The developmental patterns of wing and tail feathers of EF and LF were examined on 856 KNC from 1- to 55-day-old. The PCR was performed using K-related gene primers to confirm the match between phenotype and genotype in EF and LF chickens. In the feathering types, 744 EF chickens and 112 LF chickens were identified. The EF chicks had long primaries and coverts, and the length between primaries and coverts was distinctly different. LF chicks had shorter primaries and coverts than EF chicks. The LF chicks could be classified into four types such as LF-less, LF-scant, LF-equal and LF-reverse types according to the shape of wing feathers. In EF chicks, the difference in length between primaries and coverts increased with age. There was no difference in length between primaries and coverts in all four types of LF chicks until 15-day-old. EF chicks had 1.5 times longer in primaries than LF chicks until 15-day-old. The tail feathers of EF chicks were long and distinct at 5-day-old, but the tail feathers of LF chicks were short and unclear. Classifying with primaries lengths, 9 mm or more was regarded as EF and less than 9 mm as LF. Identifying the feathering, PCR results and phenotypes were 99% identical. In conclusion, it is possible to establish the feather-sexing strain of KNC using the sex-linked feathering characteristics. Key Words: